Efficacy and Safety of Biologics and Small Molecule Drugs in the Treatment of Ulcerative Colitis: a Network Meta-analysis - TAN Shufa, ZHANG Leichang, GAO Qiangqiang, OU Yan, HUANG Shuilan (Zhongguo quanke yixue, 2024)
Background Ulcerative colitis (UC) is a persistent immune-mediated inflammatory bowel disease characterized by chronic relapses and remissions. The management of UC remains a subject of contention, particularly as approximately half of the patients experience a complex disease progression marked by chronic activity or frequent recurrence of common UC symptoms, significantly impacting their quality of life. Objective The current landscape presents a growing array of treatment modalities for UC. This study aims to systematically compare the relative efficacy and safety of biologics and small molecule drugs in treating patients with UC. Methods Two independent researchers meticulously conducted a search for randomized controlled trials involving biologics and small molecule drugs for UC. The search encompassed PubMed, Embase, Web of Science, Cochrane Library, CNKI, Wanfang Data, and VIP. The intervention group involved either biologics or small molecule drugs, while the control group received a placebo. The quality of the included studies was assessed using the Cochrane Risk of Bias tool and RevMan 5.4. Paired analyses and network meta-analyses were conducted using R Studio. The surface under the cumulative ranking curve (SUCRA) was employed to rank the included drugs based on each outcome indicator, providing a comparative assessment of the clinical efficacy of diverse treatments for UC. Results A total of 25 studies including 9 546 patients with ulcerative colitis and 10 intervention regimens (Filgotinib 100 mg, Filgotinib 200 mg, Upadacitinib, Tofacitinib, Etrolizumab, Adalimumab, Vedolizumab, Golimumab 50 mg, Golimumab 100 mg, Infliximab). The results of SUCRA probability ranking of clinical remission effect of each drug showed that Upadacitinib (94.1%) >Vedolizumab (85.1%) >Tofacitinib (74.3%) >Infliximab (72.7%) >Filgotinib 200 mg (51.5%) >Golimumab 100 mg (44.3%) >Golimumab 50 mg (39.3%) >Etrolizumab (38.9%) >Adalimumab (29.8%) >Filgotinib 100 mg (18.7%) >Placebo (0.7%). The results of SUCRA probability ranking of the effect of each drug on clinical response showed that Upadacitinib (98.4%) >Infliximab (84.4%) >Tofacitinib (67.2%) >Vedolizumab (58.4%) >Golimumab 50 mg (53.3%) >Adalimumab (34.6%) >Golimumab 100 mg (30.1%) >Placebo (0.4%). The results of SUCRA probability ranking of the effect of each drug on endoscopic remission showed that Upadacitinib (98.7%) >Tofacitinib (68.6%) >Filgotinib 200 mg (59.6%) >Adalimumab (55.2%) >Etrolizumab (46.0%) >Vedolizumab (45.9%) >Filgotinib 100 mg (23.4%) >Placebo (2.2%). The results of SUCRA probability ranking of the effect of each drug on mucosal healing showed that Upadacitinib (99.7%) >Tofacitinib (77.2%) >Infliximab (65.2%) >Golimumab 50 mg (46.4%) >Vedolizumab (44.4%) >Adalimumab (33.8%) >Golimumab 100 mg (31.9%) >Placebo (1.0%). The results of the SUCRA probability ranking of the risk of adverse events for each drug showed that Golimumab 100 mg (96.7%) >Golimumab 50 mg (92.1%) >Placebo (68.7%) >Tofacitinib (60.8%) >Adalimumab (60.7%) >Etrolizumab (47.2%) >Upadacitinib (42.2%) >Vedolizumab (41.3%) >Infliximab (27.0%) >Filgotinib 200 mg (6.6%) >Filgotinib 100 mg (6.2%) . Conclusion Upadacitinib demonstrated optimal efficacy in clinical response, clinical remission, mucosal healing, and endoscopic remission, and Filgotinib 100 mg demonstrating safer outcomes in terms of adverse events.